Atividade antioxidante na emergência e crescimento inicial de mudas de parapiptadenia rigida (Benth.) Brenan em substratos alternativos com diferentes fontes de carbono - Marcon, Thaís Regina (2017)
The Parapiptadenia rigida is a native-tree species with fast natural regeneration, so, it has been recommended to mixed reforestation in degraded areas. The seedlings’ availability of native species in nurseries is fundamental to their management in projects of environmental recovery. The quality of nursery seedlings depends on factors such as substrate application with good quality. Organic compounds have been tested as alternative substrates for a sustainable cropping yield, to reuse organic wastes and minimize the environmental impacts. Thus, the present study aimed at evaluating the substrate influence on antioxidant enzymatic activity, for both seedlings’ emergence and initial growth of angico-red seedlings (Parapiptadenia rigida). The substrates were formulated from the composting of agroindustrial wastes with different carbon sources, totaling six treatments: commercial substrate (control); Organic cotton-based substrate; Organic substrate based on sugarcane bagasse; Organic substrate based on Napier grass; Organic substrate based on pruning of trees and organic substrate based on sawdust. The chemical and physical determinations of the studied substrates were carried out under laboratory conditions. Two trials were carried out, the first one in the laboratory, completely randomized, whose following evaluated emergence parameters of angico-red seedlings were: relative emergence frequency, emergency synchronization, emergence speed index, mean emergence time and the activity of antioxidant enzymes of angico-red seedlings. The second experiment was carried out in a greenhouse, following a design of randomized blocks. The following data of initial growth were monthly evaluated: height, stalk diameter and number of leaflets in angico-red seedlings. Root dry mass, aerial part dry mass, Dickson quality index, nutrient content, enzymatic activity and membrane damage of angico-red seedlings were recorded by the end of 120 days. Finally, the commercial substrate presented the best results for angico-red seedlings’ emergence, but during their growth, the alternative organic substrates showed advantages over the commercial one in the final development of angico-red seedlings. The organic substrates based on cotton and Napier grass provided a low percentage of emergence of angico-red seedlings, as well as the lowest root and shoot length answers, and the highest activity of peroxidase enzyme. This result has shown that an oxidative stress had occurred and the activity of repair enzymes was not enough when compared to the damages caused by the substrates. On the other hand, the organic substrates based on cane bagasse and sawdust showed the best results in emergence and development of angico-red seedlings. They also provided the highest values of Dickson`s seedlings quality index. According to these results, it is possible to assert that the organic substrates formulated by the composting from different carbon sources affected in a different way antioxidative enzymes activity of angico-red seedlings. And that the best indicated substrates to produce angico-red are based on sawdust and sugarcane bagasse.